50 years of CCRMA - Parra Cancino, Juan; 50 years of CCRMA CCRMA, Stanford University, and online 18 February 2024 (2023)
guitar, electronics
Live Stream network performance of "The Core"
FRIS
Editorial review
Keywords: Music, Thought and Technology